Multinational oil companies in Nigeria and Corporate Social Responsibility in the HIV/AIDS response in host communities - Joseph I. Uduji; Elda N. Okolo-Obasi; Simplice Asongu (African Governance and Development Institute (AGDI), 2019)
We assess the impact of corporate social responsibility (CSR) of multinational oil companies (MOCs) on HIV/AIDS prevalence in Nigeria ' s oil producing communities. One thousand, two hundred households were sampled across the rural communities of Niger Delta. Using logit model, the main result indicates that General Memorandum of Understandings (GMoUs) have not significantly impacted on factors behind the spread of HIV/AIDS in rural communities. This implies that the impact of the disease on MOCs business, employees and their families, contractors, business partners and the oil communities has not inclined downward. The findings suggest that CSR offers an opportunity for MOCs to help address HIV/AIDS prevalence through a business case for stakeholders' health in the region. It calls for MOCs to improve GMoUs health intervention on sensitization campaigns, funding testing and counselling centers, subsidizing anti-retroviral drugs, prevention of mother- to-child transmission, rehabilitation of orphaned and vulnerable children and other cares for people living with AIDS.
Keywords: J43; O40; O55; Q10; 330; corporate social responsibility; multinational oil companies; HIV/AIDS initiatives; logit model; Niger Delta